A short review on heterojunction photocatalysts: Carrier transfer behavior and photocatalytic mechanisms. (October 2021) - Yang, Hua
Graphical abstract: Highlights: How to realize the electron-hole pair separation for photocatalysts?. Properties and photocatalytic mechanisms of heterojunctions in all cases are discussed. All types of the heterojunctions are expected to exhibit enhanced photocatalytic performances. Abstract: Construction of heterojunctions by coupling two semiconductors together is one of the most efficient ways to realize the electron-hole pair separation. In this short paper, I systematically discuss the properties of heterojunction photocatalysts in all cases. The formation of space charge regions, built-in electric field and potential barriers at the interface regions of thermally equilibrated heterojunctions are analyzed in details. When the heterojunctions are used for photocatalysis, the transfer behavior and mechanism of photo-excited non-equilibrium carriers between the constituent semiconductors are discussed. It is demonstrated that the heterojunction properties, carrier transfer behavior and photocatalytic mechanism depend highly on the semiconductivity (N-type or P-type), work function (or Fermi level), and CB/VB potentials of the constituent semiconductors. All types of the heterojunction photocatalysts are expected to exhibit enhanced photocatalytic performances. This paper provides an important insight into the understanding of heterojunction photocatalytic mechanism and design of excellent heterojunction composite photocatalysts.